Kualitas Pelayanan Publik dalam Pembuatan E-KTP di Kecamatan Cimahi Selatan - Nuraini, Intan; Kurhayadi, Kurhayadi; Wargadinata, Betty (Universitas Batanghari Jambi, 2024)
This study aims to determine and analyze the quality of public services in making E-KTP at the South Cimahi District Office. The method in this study uses a type of quantitative approach method. This study uses informants, namely the public who are given services and employees who provide services. The results of this study concluded that public implementation in the South Cimahi sub-district had inhibiting factors, namely the lack of infrastructure and human resources. There is an empathy dimension with indicators of friendly manners, respect for what has been implemented, non-discrimination and prioritizing the interests of service users, but there are indicators regarding the unfriendliness of service employees who have not realized what the community expects in serving the community. The assurance dimension with indicators of certainty and timely guarantees has been realized what the community wants. This is proven by the absence of public complaints regarding indicators on the assurance dimension. The responsiveness dimension with indicators that are timely, precise, fast, responds to complaints and is thorough has been implemented. This is evidenced by the absence of complaints from the public about indicators on the responsiveness dimension. The reliability dimension has indicators of expertise, clear service standards, accuracy and ability that have been implemented, but the indicators of employee expertise in using assistive devices for services have not gone according to the expectations of service users. The tangible dimension has been implemented with indicators of the use of convenience aids, appearance and convenience, but there are indicators that have not been fully implemented regarding the convenience of service places.